Impact of Testing Temperature on the Structure and Catalytic Properties of Au Nanotubes Composites - Anastassiya A. Mashentseva; Daryn B. Borgekov; Maxim V. Zdorovets (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2018)
In the paper, the catalytic activity of composites based on gold nanotubes and ion track membranes was studied using bench reaction of the p-nitrophenol (4-NP) reduction in the temperature range of 25-40 °C. The efficiency of the prepared catalysts was estimated on the rate constant of the reaction and by conversion degree of 4-NP to p-aminophenol (4-AP). The comprehensive evaluation of the structure was performed by X-ray diffraction and scanning electron microscopy. A decreasing of the composites activity was observed when the reaction were carried out at the temperature over 35 °C, due to an increased average crystallite size from 7.31±1.07 to 10.35±3.7 nm (after 1st run). In temperature range of 25-35 °C the efficiency of the composite catalyst was unchanged in 3 runs and decreases by 24-32 % after the 5th run. At the high temperature of 40 °C after the 5th run the composite become completely catalytically inert.